Rock Art and Social Memory in the Deseado Massif: An Approach from the Study of Superimpositions in Cueva 2, Los Toldos, Santa Cruz Province, Argentina - Carden, Natalia Marina (2025)
In this work, we explore the way in which rock art mediates social memory. Our study case is based on the rock art sequence established for Los Toldos archaeological locality, Argentina, which begins in the Pleistocene/Holocene transition and extends to the Late Holocene. The analysis focuses on superimpositions, with an emphasis on the human attitudes towards previous images. Despite changes detected along the sequence, Los Toldos manifests a strong emphasis on recalling the past, which is evidenced by the superimposition, replication, maintenance and recycling of motifs. These behaviors show a multi-generational dialogue that kept an ancestral memory alive but also recreated it through grouping images from different times for telling stories. This study places an emphasis on the users/consumers of rock art rather than on its makers. This focus narrows the gap between the archaeological record and the ethnographic sources by claiming that the Tehuelche people were engaged with rock art even though they did not make it.